Relationships of Career Self-Efficacy Expectations to the Myers-Briggs Type Indicator and the Personal Styles Scales - Tuel, Beverly D.; Betz, Nancy E. (Measurement and evaluation in counseling and development)
The significant correlations between the scales of the Skills Confidence Inventory (Betz, Borgen, & Harmon, 1996), a measure of self-efficacy expectations with respect to the 6 Holland themes, and those of the Myers-Briggs Type Indicator (Myers & McCaulley, 1985) and the Personal Styles Scales of the Strong Interest Inventory (Harmon, Hansen, Borgen, & Hammer, 1994) support the construct validity of all 3 inventories.